2017
DOI: 10.1111/are.13429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary docosahexaenoic acid sources, microalgae meal and oil, on growth, fatty acid composition and docosahexaenoic acid retention of orange-spotted grouper,Epinephelus coioides

Abstract: This study evaluated the effects of Aurantiochytrium spp. microalgae meal and oil as dietary docosahexaenoic acid (DHA) sources on the growth, fatty acid composition and DHA retention of orange-spotted grouper, Epinephelus coioides. Dietary fish oil was replaced with microalgae meal or oil to provide an equal amount of DHA as a fish oil-containing basal diet. In total, three experimental diets were fed to triplicate groups of fish (initial wt: 8.48 AE 0.06 g) in a recirculating system for 8 weeks. The weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The complete replacement of FO using Aurantiochytrium sp. oil/meal has been undertaken in salmonids (Miller et al 2007;Kousoulaki et al 2015), tilapia (Sarker et al 2016;Brignol et al 2018), olive flounder Paralichthys olivaceus (Qiao et al 2014), giant grouper Epinephelus lanceolatus (García-Ortega et al 2016), and orange-spotted grouper E. coioides (Lee et al 2017). The absence of a negative effect was also confirmed on the growth performance of longfin yellowtail fed with an algal meal (AM)-supplemented fish meal (FM)-based diet and FMreplaced diets .…”
Section: Introductionmentioning
confidence: 96%
“…The complete replacement of FO using Aurantiochytrium sp. oil/meal has been undertaken in salmonids (Miller et al 2007;Kousoulaki et al 2015), tilapia (Sarker et al 2016;Brignol et al 2018), olive flounder Paralichthys olivaceus (Qiao et al 2014), giant grouper Epinephelus lanceolatus (García-Ortega et al 2016), and orange-spotted grouper E. coioides (Lee et al 2017). The absence of a negative effect was also confirmed on the growth performance of longfin yellowtail fed with an algal meal (AM)-supplemented fish meal (FM)-based diet and FMreplaced diets .…”
Section: Introductionmentioning
confidence: 96%
“…Over the past two decades, there has been great research progress on grouper nutrition and feeds (Feng et al, 2020). In terms of the dietary utilization of lipid/FAs in fish species, a series of reports have been published (An et al, 2020;Chen et al, 2017;Lee et al, 2018;Li, Mai, et al, 2016;Luo et al, 2005). So far, however, there are few studies on the utilization effect of VOs used to substitute FO in grouper diets (Lin et al, 2007;Tseng & Lin, 2020;Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Sc oil in marine fish have been reported in Atlantic salmon and Pacific white shrimp (Miller, Nichols, & Carter, 2007; Nonwachai, Purivirojkul, Chuchird, & Limsuwan, 2009), while there were few studies on Sc oil in freshwater fish feed. In the study of orange‐spotted grouper ( Epinephelus coioides ), it was pointed out that the retention of DHA in microalgae oil by fish was higher than that of dry microalgae meal, indicating that the cell wall contained in microalgae meal affected the absorption of DHA, and removal of cell walls could improve the utilization of DHA‐rich microalgae (Lee, Zhuo, & Lin, 2018). This study indicated that adequate dietary n‐3LC PUFA supplementation significantly improved growth performance of grass carp.…”
Section: Discussionmentioning
confidence: 99%